GAYA KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR KECAMATAN TUMIJAJAR KABUPATEN TULANG BAWANG BARAT - Robi Romansyah; Agus Purnomo; Edward Antony (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) How to apply the leadership style of Camat in improving the performance of employees in Tumijajar Sub-district of West Tulang, (2) What aspects support and inhibit the application of style The leadership of Camat in improving the performance of employees in the district office of Tumijajar regency of West Garlic, (3) What aspects have been and should be implemented in addressing the constraints/problems of applying the leadership style of Camat in order Improving employee performance in Tumijajar sub-district of West Tulang. The research methods used in this study are using qualitative research types with descriptive analytical methods. The use of this method is to examine and describe qualitatively, how to apply the leadership style of Camat in improving the performance of employees in Tumijajar Sub-district of West Tulang. All data are obtained directly from the informant in the field using interviews and observation techniques, according to the research objectives. The results showed that the application of the leadership style of Camat in improving the performance of employees in Tumijajar Sub-district Office of West Onion, through the dimensions (1) Telling (high duty and low relations), (2) Selling (task High and high Relationships), (3) Participating (High relationship and low-duty), (4) Delegating (relationships and low-duty), all have been implemented in accordance with existing situations and conditions, but not optimal because of the lack of resource capabilities Human beings, (staff) in understanding leadership styles conducted by leaders, although the often-applied leadership styles are tailored to existing job conditions and employees are still given the opportunity to innovate in carrying out tasks Provided by the leadership so that they are more in charge of carrying out the tasks they are charged